A teoria da interpretação e as decisões discricionárias: a hermenêutica filosófica como aliada do pragmatismo jurídico no combate à crise legislação versus jurisdição - Tsuchiya, Gustavo Shiguetomi (2021)
Legal positivism, in the figure of its most prominent, Hans Kelsen, proposes the Pure Theory of Law. This legal approach separates Law as an autonomous science, performing an epistemological and axiological cut. Law is a complex of legal rules in a hierarchical legal system, and the jurist must study only these rules, using logic as his method. The relationship between people is established in a relationship of legal norms, in which the subject is separated from the object. One of the problems brought by the Pure Theory of Law is the magistrate's decision not to be bound to the interpretations made by jurists or doctrinaires, being free to decide according to the best interpretation that suits him or her. Hence, the problem arises of each magistrate judging in his own way, since the judicial decision is an "act of will". Thus, to combat and better clarify what legal positivism proposes and the problem of the magistrate's act of will, the pragmatic theory of law stands out, as proposed by Tercio Sampaio Ferraz Jr. The pragmatic theory characterizes the legal norm as a message from both the one who is sending it and the one who is receiving it. The relationship in the pragmatics of law becomes one between subjects, and the legal norm has a commitment aspect and a report aspect, being a message and a discourse coming from a legitimate and empowered authority in which one can interpret. And legal interpretation consists of a power of symbolic violence that aims to standardize the meaning of the legal norm. It is a power of control and influence capable of imposing meanings as legitimate, just, and consensual, and of neutralizing other interpretations. To combat the discretion of the magistrate, the interpretations of authority, reputation, and leadership are used, forming a consensus, that is, a power of symbolic violence. In relation to the interpretations of the Law, it is necessary to join forces with the so-called Philosophical Hermeneutics, which in Brazil has Lenio Streck as its greatest representative. The philosophers Martin Heidegger and Hans-Georg Gadamer basically describe the hermeneutic method itself, whose basic principles are ontological differences, hermeneutic circle and the interpreter's expanding function. From there arises the application in the Law, because the texts, most of the time, come written, and the hermeneutic method arises to understand and clarify that which was hidden in the legal norm. For this reason, Lenio Streck differentiates between text and rule, being "entity" (described text) and "being" (legal rule) - in other words, what the rule "really" means. Applied to the concrete case, there is a correct answer for every judicial decision. From this perspective, the contraposition between "objective and subjective", "being" and "being", "fact" and "right", through the fusion of horizons, and the hermeneutic circle manages to be a great ally against the discretion of the magistrate